The The Contemporary Relevance of the Principles, Values, and Ideals that Shaped Assam’s Freedom Movement - Miller, Leon (Journal of History Culture and Art Research, 2023)
This article explains the connection between the vision that inspired India’s freedom and what is recognized today as essential values and principles for making freedom, justice, self-determination, and peace possible. The article focuses on the discourse of Assam’s movement as a methodology for determining the principles that shaped the movement and developing a theoretical framework on the movement. This is compared with what is celebrated today as essential principles of human rights, justice, sustainability, and self-determination. Assam contributed an integrative approach to freedom and self-determination that, although met with resistance, is now regarded as a state-of-the-art model for realizing the goals that human social action aims to achieve. The article not only stresses the principles, values, and ideals of the freedom movement but indicates their relevance for shaping the future and as a unifying force. It also explains a state-of-the-art means for fully realizing the future envisioned by the movement. The article adds to the historical analysis of the freedom movement by indicating its contribution to a new discourse on social, cultural, and sustainable development.